Achieving equity in dialysis care and outcomes: The role of policies. Issue 1 (3rd January 2020) - Crews, Deidra C.; Novick, Tessa K.
Abstract: Socially disadvantaged persons, including racial and ethnic minorities, individuals with low incomes, homeless persons, and non‐US citizens bear a disproportionate burden of end‐stage kidney disease (ESKD). Inequities in nephrology referral, vascular access, use of home dialysis modalities, kidney transplantation, and mortality are prominent. Public policies, including the Patient Protection and Affordable Care Act, end‐stage renal disease Quality Incentive Program, and the Prospective Payment System, were enacted to improve healthcare access and dialysis care. Here, we highlight inequities in dialysis care and outcomes, how current ESKD and other public policies may influence or exacerbate these inequities, and gaps in the literature needed to inform future policies toward achieving equity in ESKD. We give special attention to the 2019 Advancing American Kidney Health Executive Order, which has high potential to radically transform dialysis care.